The Effect of Motivation and Interaction Effects on Improving Mathematical Comprehension Skills through Problem and Inquiry-Based Learning - Supriatna, Irfan; Wahyudin, Wahyudin; Turmudi, Turmudi; Yasing, Hakimee (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2024)
This study investigates the influence of motivation levels and interaction effects on students' Mathematical Comprehension Ability (KPM) while utilizing Problem-Based Learning (PBL) and Inquiry-Based Learning (IBL). Employing a quasi-experimental with the 3x2 factorial design, the research was conducted with fourth-grade students in Ciamis Regency, West Java. The findings indicated that the average KPM increase for students using PBL was 53%, which is considered moderate, whereas for IBL, it was 29%, which is categorized as low. Significantly, there were variations in learning effects between PBL and IBL (p < 0.001), with PBL demonstrating a more pronounced impact on KPM improvement. However, the influence of motivation level on KPM improvement was deemed insignificant (p = 0.192), as was the interaction effect between learning methods and motivation level on KPM improvement (p = 0.057). In conclusion, the study suggests that PBL is more effective than IBL in enhancing students' KPM. At the same time, motivation level does not significantly influence KPM improvement, and there is no interaction effect between the type of learning method and motivation level on KPM improvement.